OPTIMALISASI LAHAN PEKARANGAN DENGAN BUDIDAYA IKAN LELE UNTUK MENINGKATKAN PENDAPATAN MASYARAKAT - Rusnandari Retno Cahyani; Anniez Rachmawati Musliffah (Universitas Muhammadiyah Semarang, 2017)
Science Program for the Community aims to implement “tri dharma” college in terms of community service in helping partners provide solutions to the problems faced in optimizing the yard land. This IbM program applies educational methods that involve the active participation of “Tani Mulyo I group, withsome members already breeding catfish. Activities include (1) socialization, (2) efficient and safe pondmaking training, (3) training on the introduction and processing of fish feed from surrounding waste. Outcomes from this program can form an independent business group of catfish breeders, able to managethe business properly, can make alternative feed and able to apply feed technology. The stages of the implementation oftraining and mentoring include the formulation stage. The resultof this dedication activity is to optimize the yard land owned by the community of devoted partners, empower the potentialpartners to increase the income of the community, increase the knowledge information about the manufacture of fish ponds from “terpal”, and feed management.Keywords: IbM, Optimalisasi lahan, Budidaya lele, Pendapatan masyarakat